Diksi Dalam Novel Bekisar Merah Karya Ahmad Tohari Kajian Stilistika Dan Implementasinya Sebagai Bahan Ajar Di SMA - Khotimah, Siti Kusnul (2016)
Khotimah, Siti Kusnul, S200120066, Magister of Indonesian Language Study, School of Postgraduate, Muhammadiyah University of Surakarta, 2015, 115 pages. The purpose of this study are four. (1) Decribing socialhistory of the author. (2) Describing the dictions in Ahmad Tohari's novel Bekisar Merah by using stylistic study. (3) Describe the meaning diction in Ahmad Tohari's novel Bekisar Merah by using stylistic study. (4) Describing the implementation if the diction in Ahmad Tohari's novel Bekisar Merah by using stylistic study as teaching material of Bahasa Indonesia in Senior High School. The techniques of data collection are library technique, paying a good attention, and making notes. The technique of data analysis used the semiotic reading which consists of heuristic and hermeneutic reading. The result of this study is the advantage of the diction in Ahmad Tohari's novel Bekisar Merah. The diction which occurred in Ahmad Tohari's novel Bekisar Merah are (a) connotative words, (b) concrete words, (c)absorption words of foreign language, (d) remarkable greetings (e) Javanese exclamation words, (f) vulgar words, and (g) Javanese language vocabulary. The meanings of the diction in Ahmad Tohari's novel Bekisar Merah are divided into three points. They are (a) moral deviation problems, (b) poverty, (c) and political issues. The implementation of the diction in Ahmad Tohari's novel Bekisar Merah as the teaching material of Bahasa Indonesia in Senior High School can be correlated to the fourth main competence, processing, logical thnking and presenting in concrete and abstract circumstances. It can be related to the development which is studied at school independently and is able to use the method which appropriate to the scientific rules. It is also can be correlated to the indicator 4.5 which is about making the complex procedural text (connotative words, remarkable greetings, Javanese exclamation words, vulgar words, concrete words, absorption words of foreign language in anecdote text) Key words: diction, Bekisar Merah novel, stylistic study, teaching material of Bahasa Indonesia in Senior High School